Dynamic Meso-Scale Anchorage of GPI-Anchored Receptors in the Plasma Membrane: Prion Protein vs. Thy1 - Nemoto, Yuri L. (Cell Biochem Biophys, 2017)
The central mechanism for the transmission of the prion protein misfolding is the structural conversion of the normal cellular prion protein to the pathogenic misfolded prion protein, by the interaction with misfolded prion protein. This process might be enhanced due to the homo-dimerization/oligomerization of normal prion protein. However, the behaviors of normal prion protein in the plasma membrane have remained largely unknown. Here, using single fluorescent-molecule imaging, we found that both prion protein and Thy1, a control glycosylphosphatidylinositol-anchored protein, exhibited very similar intermittent transient immobilizations lasting for a few seconds within an area of 24.2 and 3.5 nm in diameter in CHO-K1 and hippocampal neurons cultured for 1- and 2-weeks, respectively. Prion protein molecules were immobile during 72% of the time, approximately 1.4× more than Thy1, due to prion protein’s higher immobilization frequency. When mobile, prion protein diffused 1.7× slower than Thy1. Prion protein’s slower diffusion might be caused by its transient interaction with other prion protein molecules, whereas its brief immobilization might be due to temporary association with prion protein clusters. Prion protein molecules might be newly recruited to prion protein clusters all the time, and simultaneously, prion protein molecules in the cluster might be departing continuously. Such dynamic interactions of normal prion protein molecules would strongly enhance the spreading of misfolded prion protein.